Comprehensive Evaluation of TLR4 and Cytokine Profiles in Patients Infected with Entamoeba histolytica - Hasan, Torken Ahmed Hama (American Journal of Biology and Natural Sciences, 2025)
The current research aimed at systematically identifying the values of Toll-Like Receptor four (TLR4) and the trend of expression of some immune cytokines (IL-1b, IL-6, TNF-a, IL-10, IFN-g) in an entamoeba histolytica-infected patient with amebic liver abscess (ALA) and with amebic colitis (AC) versus healthy controls. The blood sample analyses were conducted on the blood samples using the sophisticated techniques such as enzyme immunoassay (ELS), the western blot and the flow cytometry processes to correlate these disease markers depending on the intensity of the disease. Twenty healthy people were used as a control group, 30 patients with ALA and 30 patients with AC were incorporated. The findings indicated that the ALA patients had a greater up-regulation of TLR4 along with the expression of pro-inflammatory cytokines (IL-1b, IL-6, TNF-a, IFN-g) in comparison with the AC patients and controls which meant that there was a high inflammatory immune response which was associated with severe infection. However, the anti-inflammatory cytokine IL-10 was relatively increased in AC patients, which indicated that it may play important roles in inflammation control for the defense of tissue. Moreover, clinical symptoms correlated positively with higher inflammatory markers, respectively proving a stronger correlation in severe ALA cases.These results indicate that TLR4 and the studied cytokines are potential biomarkers for severity of onset of Entamoeba histolytica infection and could be useful in the implementation of future diagnostic and therapeutic approaches based on modulation of immune responses to limit tissue damage and preserve an effective host defence. These results enrich the importance of pro-and anti-inflammatory cytokine balance for determining the end of the disease and this study suggests internalization of these biomarkers for early diagnosis and immune-target therapy.